Analisis Kepuasan Pelanggan dengan Menggunakan Metode 7P pada Kedai AA - Inova Klara Saragih; Andhyka Tyaz Nugraha; Rizqi Wahyudi (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
Kedai AA is one of the culinary businesses that is experiencing increasingly fierce competition, the competition that occurs is due to the increasing number of businesses that are similar to Kedai AA. In facing this competition, it is necessary to have a marketing mix to be able to encourage the level of customer satisfaction which is able to increase profits for each business. The goal to be achieved from this study is to find out and see how the relationship between the 7P independent variables has on customer satisfaction at the AA store. The approach used in this study is a quantitative approach by distributing questionnaires to customers at the AA shop using a Likert scale. In this study the population used was all customers at the AA Store with a sample of 110 respondents who were chosen deliberately and randomly with the criteria of being a customer of the AA Store. This study uses data testing methods through validity and reliability tests, and the SEM method is the method used to analyze data. The results obtained in this study are product variables have no relationship to customer satisfaction, price has an insignificant relationship, several other variables have a significant relationship, and all variables together have a relationship to customer satisfaction.